Determination of salt contents of bread types and estimation of salt intake from bread in Lebanon - Nathalie Barakat; Ammar Olabi; Lara Nasreddine; Hussain Ismaeel; Samer Kharroubi; Layal Abou Jaoude; Mona Zeidan; Caroline Rajeh; Imad Toufeili (PLoS ONE, 2025)
Background High dietary salt intake is a major risk factor for hypertension, which strongly predisposes affected individuals to cardiovascular diseases and stroke. Most populations consume more salt than the upper limit set by the WHO at 5 g/day. Bread is a major contributor to salt intake, and reducing bread salt is the most effective approach for reducing the ingestion of salt by populations. Aims This work aims to determine the salt levels of bread marketed in Lebanon, bread consumption by the Lebanese population, and the bread’s contribution to daily salt intake. Methods One hundred and sixty-two samples of the breads consumed in Lebanon were collected from 45 bakeries, and their salt levels were determined by atomic absorption spectrophotometry. The bread consumption was estimated from a cross-sectional survey of 1048 individuals, and their salt intakes were computed using the determined levels of bread salt. The proportion of breads samples meeting the WHO-recommended salt levels was computed, and the salt intakes were determined and benchmarked against the WHO cut-offs. Results The least salty and saltiest breads were the white pita and markouk, with mean salt levels of 1.46g/100g and 2.77g/100g, respectively. The breads meeting the WHO-recommended salt levels ranged between 7.1% and 12%. The total bread consumption was 176.27 ± 216.73 g/day with white pita being the most consumed at 96.63 ± 175.44 g/day. The salt intake from bread at 2.86 ± 3.83 g/day amounted to 57.2% of the WHO limit for daily salt intake. Conclusions The breads spanned wide ranges of salt content and differed markedly in their contribution to salt intake. White pita was the most consumed and contained the least salt thereby making it the chief contributor to salt intake from bread. Interestingly, the analyzed breads indicated the availability of products that meet the WHO-recommended targets for salt thereby providing an impetus for reducing bread salt by stealth.